2018
DOI: 10.4244/eij-d-17-00332
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bioresorbable versus permanent polymer on longterm vessel wall inflammation and healing: a comparative drug-eluting stent experimental study

Abstract: BP-EES resulted in a lower net long-term reduction in neointimal formation and inflammation compared to permanent polymer DES in an animal model. Further study of the long-term neointima formation deserves study in human clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nevertheless, preclinical work in the most preferred large animal model, that is, the porcine coronary artery model remains of vital interest during the earlier DES development process. 5,6 In addition, today’s intravascular imaging techniques do not allow a differentiation between endothelial cells and fibrin coating of the stent struts in the clinical setting. Therefore, the time course of endothelialization in the porcine model is a major indicator in preclinical DES research.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, preclinical work in the most preferred large animal model, that is, the porcine coronary artery model remains of vital interest during the earlier DES development process. 5,6 In addition, today’s intravascular imaging techniques do not allow a differentiation between endothelial cells and fibrin coating of the stent struts in the clinical setting. Therefore, the time course of endothelialization in the porcine model is a major indicator in preclinical DES research.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the polymer was completely dissolved, and the less inflammatory bare metal surface came into direct contact with the vascular wall, accommodating relatively healthy and homogeneous neointimal tissue growth for the remainder. In addition, Wilson et al [23] demonstrated that the use of a bioresorbable-polymer coating as a method for drug elution results in lower long-term inflammation compared to durable polymer DES. Furthermore, Itoh et al [24] showed that qualitatively and quantitatively consistent neointimal stent coverage was achieved by the 12-month time point by optical frequency-domain imaging.…”
Section: Discussionmentioning
confidence: 99%
“…PF-DES were introduced with the aim to overcome the risks of late safety and efficacy outcomes associated with the preceding generations of devices. The polymer coating used in DP-DES has been shown to cause chronic inflammation and delayed vascular healing [ 30 ]. A meta-analysis [ 31 ] of 6575 patients reported that PF-DES had a significantly reduced risk of all-cause death compared with DP-DES (OR, 0.77; 95% CI, 0.61–0.98; P = 0.03).…”
Section: Discussionmentioning
confidence: 99%